IMPLEMENTATION OF TECHNOLOGY-BASED LEARNING BY PRE-SERVICE TEACHERS DURING TEACHING PRACTICE PROGRAM - Arochman, Taufik; Fortinasari, Paulina Besty (Premise: Journal of English Education and Applied Linguistics, 2024)
Technology integration in classroom has become an important component for pre-service teachers in Teaching Practice Program (TPP). This situation makes technology become a basic need for instructors and also the students. The objective of this study is to identify the readiness of pre-service teachers in implementing technology in teaching and learning activities in the classroom. The method used in this study was qualitative research. Participants of the study were 50 pre-service teachers in Magelang and Temanggung Regencies, Central Java, Indonesia. The data were gathered using observation, questionnaires, and interviews. The results showed that most of the pre-service teachers were ready to face the challenges of applying technology in their classroom. Most of them have recognized the applications, software, and websites that can be integrated to the teaching and learning activities such as Slides, PowerPoint, Prezi, PowToon, and Canva. Moreover, most of students are familiar with and are even accustomed to using modern and complex applications that support teachers to improve students' English language skills such as Google Classroom, WhatsApp, WebEx Cisco, Google Meet, and Zoom. However, it is still very much needed so that students can integrate these applications into effective and meaningful learning.